2019
DOI: 10.1002/app.47902
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic nanoparticles incorporated in polyacrylonitrile‐based mixed matrix membranes for hydrophilic, ultrafast, and fouling‐resistant ultrafiltration

Abstract: Mixed matrix membrane (MMM) structures and performances are greatly affected by the distribution of nanoparticles in the polymeric matrix. Until now, there has been little research on the effects of nanoparticle distribution states on polyacrylonitrile (PAN)‐based MMM structures and performances. In this paper, different intermolecular interactions between nanoparticles and PAN molecules were generated by in situ fabricated amino‐functionalized SiO2 and TiO2 nanoparticles to create absolutely different distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…It should be noted that the smaller contact angle of PAN@Zn than that of the bare Zn can be ascribed to the spreading of water on the PAN membrane. [ 77 ] The PANZ membrane exhibits a high ionic conductivity (2.4 mS cm −1 , Figure S2D, Supporting Information), which is similar to the previously reported, [ 78 ] indicating the fast Zn 2+ transport through the PANZ layer. The better wettability facilitates the even distribution of zinc‐ion flux on the zinc's surface during cycling, which reduces the ions’ motion resistance and promotes uniform zinc electrodeposition.…”
Section: Resultssupporting
confidence: 86%
“…It should be noted that the smaller contact angle of PAN@Zn than that of the bare Zn can be ascribed to the spreading of water on the PAN membrane. [ 77 ] The PANZ membrane exhibits a high ionic conductivity (2.4 mS cm −1 , Figure S2D, Supporting Information), which is similar to the previously reported, [ 78 ] indicating the fast Zn 2+ transport through the PANZ layer. The better wettability facilitates the even distribution of zinc‐ion flux on the zinc's surface during cycling, which reduces the ions’ motion resistance and promotes uniform zinc electrodeposition.…”
Section: Resultssupporting
confidence: 86%
“…This result is rationalized with the fact that M1 and M8 had the highest values of pore density (4.8 × 10 13 m −2 and 3.5 × 10 13 m −2 ) and surface porosity (2.98% and 2.02%) among all membranes, which promoted the achievement of high water permeability, as also reported by previous studies. 71,73,82,83 By adding amphiphilic additives PVC-g-PEGMA, the antifouling properties were enhanced to a great extent and membranes retained high SA rejection rates, but the presence of the amphiphilic polymer resulted in lower pure water permeability of the membrane. To overcome this problem, a nonwoven PET may be used as support layer to increase the surface porosity and thus the permeability.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Moreover, the functionalization of these nanoparticles increases their dispersion and the hydrophilic characteristics of the membrane. As well, the previous studies demonstrated that inorganic nanoparticles such as silica (SiO 2 ) [ 11 , 12 , 13 , 14 ], zeolites [ 15 , 16 ], metal oxide (Al 2 O 3 , TiO 2 , ZnO) [ 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], and carbon nanotubes [ 23 , 24 ] could improve the hydrophilicity of the modified polymer hydrophobic membranes. Silica nanoparticles have chemical compatible and the mechanical stability needed for preparation of polymeric membrane, and their structure can be changed by chemical functionalization [ 25 ].…”
Section: Introductionmentioning
confidence: 92%